The ABC of weed management in cassava production in Nigeria: a training manual - Atser, G.; Dixon, A.; Ekeleme, F.; Chikoye, David; Dashiell, Kenton E.; Ayankanmi, T.G.; Hauser, S.; Agada, M.; Okwusi, M.; Sokoya, G.; Olorunmaiye, P.; Olojede, A.; et al. (International Institute of Tropical Agriculture, 2017)
This guide is in response to demands from cassava stakeholders on the Cassava Matters WhatsApp group and the Knowledge Attitude and Practices study (KAPs) that was conducted by the IITA-led Cassava Weed Management Project. This easy-to-read reference manual for farmers will help them to cultivate cassava better and increase their productivity. The three dimensions of weed control: cultural, mechanical, and chemical are captured and illustrated in a logical and simplified manner. Our aim is that farmers and other extension service actors reading this guide will be properly informed about critical aspects of cassava cultivation, and will be able to pass on this information to others. This material primarily belongs to the IITA Cassava Weed Management Project that is funded by the Bill & Melinda Gates Foundation. The mention of specific companies or products of manufacturers, whether or not these have been registered, does not imply that these have been endorsed or recommended by the IITA Cassava Weed Management Project in preference to others of a similar nature that are not mentioned. We encourage the use, reproduction, and dissemination of materials in this information product. Except where otherwise indicated, materials may be copied, downloaded, and printed for private study, research and teaching purposes, or for use in non-commercial products or services, provided that appropriate acknowledgment of the IITA Cassava Weed Management Project as the source and copyright holder is given.